2023
DOI: 10.1021/jacs.2c10988
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Interlocking Enhances the Electrocatalytic Oxygen Reduction Activity and Selectivity of Molecular Copper Complexes

Abstract: Efficient O2 reduction reaction (ORR) for selective H2O generation enables advanced fuel cell technology. Nonprecious metal catalysts are viable and attractive alternatives to state-of-the-art Pt-based materials that are expensive. Cu complexes inspired by Cu-containing O2 reduction enzymes in nature are yet to reach their desired ORR catalytic performance. Here, the concept of mechanical interlocking is introduced to the ligand architecture to enforce dynamic spatial restriction on the Cu coordination site. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Unfortunately, most of HVOs are unstable or inactive at the cathodic potential for ORR/HER (U < 1.23 V vs RHE for ORR and U < 0 V vs RHE for HER), although some bifunctional activities of HVOs are recently reported, such as Ir/Ni(OH) 2 (HER/OER: Ir 5+ ) [123] and Mg-doped LaNiO 3 nanofibers (ORR/OER: Ni 3+/4+ ). [124] Specific structures with multi-phases, such as core-shell structures and coordinated hybrids or complexes, [125,126] may be developed to stabilize the high-valence metal sites at the cathodic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of HVOs are unstable or inactive at the cathodic potential for ORR/HER (U < 1.23 V vs RHE for ORR and U < 0 V vs RHE for HER), although some bifunctional activities of HVOs are recently reported, such as Ir/Ni(OH) 2 (HER/OER: Ir 5+ ) [123] and Mg-doped LaNiO 3 nanofibers (ORR/OER: Ni 3+/4+ ). [124] Specific structures with multi-phases, such as core-shell structures and coordinated hybrids or complexes, [125,126] may be developed to stabilize the high-valence metal sites at the cathodic potential.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Among MIMs, catenanes are a class of interlocked molecules and are fascinating due to their molecular topologies. In recent times, many applications, such as in catalysis, [7] photo-catalysis, [8] as electro catalyst, [9] a catalyst for click reaction, [10] memory device, [11] and guest molecule encapsulation, [12] etc. have surfaced for this class of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cells (PEMFCs) are considered to be promising sustainable energy systems which can efficiently convert the chemical energy of hydrogen into electrical energy . Nevertheless, the oxygen reduction reaction (ORR), involving multiple electron and proton transfers at the cathode, limits the application of PEMFCs owing to the sluggish kinetics. Currently, Pt-based catalysts are still the most essential catalysts for the ORR, demonstrating excellent activity and durability in acidic electrolytes. , Due to the scarcity of platinum resources and the high cost, the activity of Pt-based catalysts should be urgently improved to reduce the platinum loading in catalysts . Previous studies have revealed that alloying Pt with other transition metals (TMs) is one of the most effective methods for optimizing the surface electronic structure to promote the electrocatalytic performance of Pt-TM catalysts. Despite the considerably improved ORR activities, Pt-TMs alloys are commonly prepared as face-centered cubic (fcc)-type solid solution structures, which limits the stability of the TMs under the acidic ORR conditions, thus compromising the advantages of the TMs in Pt-TM alloys. , …”
Section: Introductionmentioning
confidence: 99%